Elaboración e implementación del curso virtual de la asignatura de lengua y literatura, para el noveno año de educación general básica, del colegio nacional 26 de Noviembre, de la ciudad de Zaruma periodo 2013-2014 - Córdova Tituana, César Oswaldo (2016)
Currently, the Information and Communication Technologies (ICT) in education have shown great support in the process of learning, but most of the teachers of the National School November 26 City Zaruma unaware of the use of technologies for teaching process, therefore, it has proposed the development of a virtual learning environment (EVA). The overall objective is to develop a virtual course with a constructivist approach and its implementation to the virtual learning environment Moodle (LMS), led to the subject of Language and Literature ninth year of basic general education, framed in the levels set by the Ministry of Education and the National Association executed on November 26 in the city of Zaruma. To do the job the waterfall methodology was used to obtain the relevant information, he spoke with the teacher of the course of Language and Literature to meet the educational shortcomings. Then he designed and developed the Virtual Course, which includes the evaluation of Virtual Course to the implementation of surveys 37 students and teachers considering teaching and technical aspects with satisfactory results.